Effects of epidermal growth factor on the proliferation and cell cycle regulation of cultured human amnion epithelial cells - Fatimah, SS; Tan, GC; Chua, KH; Tan, AE; Hayati, AR (Soc Bioscience Bioengineering Japan, 2024)
Human amnion epithelial cells (HAECs) hold great promise in tissue engineering for regenerative medicine. Large numbers of HAECs are required for this purpose. Hence, exogenous growth factor is added to the culture medium to improve epithelial cells proliferation. The aim of the present study was to determine the effects of epidermal growth factor (EGF) on the proliferation and cell cycle regulation of cultured HAECs. HAECs at P1 were cultured for 7 days in medium containing an equal volume mix of HAM's F12: Dulbecco's Modified Eagles Medium (1:1) supplemented with different concentrations of EGF (0, 5, 10, 20, 30 and 50 ng/ml EGF) in reduced serum. Morphology, growth kinetics and cell cycle analysis using flow cytometry were assessed. Quantitative gene expression for cell cycle control genes, pluripotent transcription factors, epithelial genes and neuronal genes were also determined. EGF enhanced HAECs proliferation with optimal concentration at 10 ng/ml EGF. EGF significantly increased the proportion of HAECs at S- and G2/M-phase of the cell cycle compared to the control. At the end of culture, HAECs remained as diploid cells under cell cycle analysis. EGF significantly decreased the mRNA expression of p21, pRb, p53 and GADD45 in cultured HAECs. EGF also significantly decreased the pluripotent genes expression: Oct-3/4, Sox2 and Nanog; epithelial genes expression: CK14, p63, CK1 and Involucrin; and neuronal gene expression: NSE, NF-M and MAP 2. The results suggested that EGF is a strong mitogen that promotes the proliferation of HAECs through cell cycle regulation. EGF did not promote HAECs differentiation or pluripotent genes expression. (c) 2012, The Society for Biotechnology, Japan. All rights reserved.